1972
DOI: 10.1128/jb.110.2.706-721.1972
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of L Cells andChlamydia psittaci: Entry of the Parasite and Host Responses to Its Development

Abstract: The entry and development of Chlamydia psittaci in the L cell was studied by using purified, infectious parasites at high multiplicity. Entry of the parasite was accomplished by an act of phagocytosis by the host which was independent of an adsorption stage but was temperature-dependent. Kinetic VOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
193
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(197 citation statements)
references
References 32 publications
(25 reference statements)
4
193
0
Order By: Relevance
“…The unrooted tree is a based on a recent survey of chlamydial diversity in metagenomic and amplicon datasets (Lagkouvardos et al, 2014). cantly in size and shape (Siegl & Horn, 2012). The infective stage of Chlamydiaceae is usually considerably smaller than the replicative stage (0.3 lm for EBs compared with 1.0 lm for RBs in the case of C. trachomatis ;Friis, 1972;Matsumoto, 1988;Moulder, 1991;Abdelrahman & Belland, 2005), yet a similarly pronounced size distinction between the two developmental forms is not commonly observed for environmental chlamydiae. While EBs of members of the Chlamydiaceae, Parachlamydiaceae, and Waddliaceae are usually coccoid, the infective stages of some environmental chlamydiae have been described as being rod-shaped, head-and-tail or star-shaped (Kahane et al, 2001(Kahane et al, , 2002Kostanj sek et al, 2004;Michel et al, 2005;Thomas et al, 2006;Corsaro et al, 2007Corsaro et al, , 2009Karlsen et al, 2008).…”
Section: The Chlamydial Developmental Cyclementioning
confidence: 99%
“…The unrooted tree is a based on a recent survey of chlamydial diversity in metagenomic and amplicon datasets (Lagkouvardos et al, 2014). cantly in size and shape (Siegl & Horn, 2012). The infective stage of Chlamydiaceae is usually considerably smaller than the replicative stage (0.3 lm for EBs compared with 1.0 lm for RBs in the case of C. trachomatis ;Friis, 1972;Matsumoto, 1988;Moulder, 1991;Abdelrahman & Belland, 2005), yet a similarly pronounced size distinction between the two developmental forms is not commonly observed for environmental chlamydiae. While EBs of members of the Chlamydiaceae, Parachlamydiaceae, and Waddliaceae are usually coccoid, the infective stages of some environmental chlamydiae have been described as being rod-shaped, head-and-tail or star-shaped (Kahane et al, 2001(Kahane et al, , 2002Kostanj sek et al, 2004;Michel et al, 2005;Thomas et al, 2006;Corsaro et al, 2007Corsaro et al, , 2009Karlsen et al, 2008).…”
Section: The Chlamydial Developmental Cyclementioning
confidence: 99%
“…They also recruit the host's rough endoplasmic reticulum (rER), eventually resulting in a translocation of rER proteins into the inclusion (Dumoux et al, 2012). Mitochondria are recruited to the inclusions of C. psittaci and Waddlia chondrophila (Friis, 1972;Peterson and de la Maza, 1988;Matsumoto et al, 1991;Croxatto and Greub, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the genus Chlamydia are obligate intracellular parasites with a unique growth cycle [1]. After attachment to the surface of susceptible cells, the bacteria are internalized into host cells by a process sensitive to inhibitors of glycolysis [2] and oxidative phosphorylation [3], but resistant to cytochalasin B [4]. This suggests that the ingestion of chlamydiae is a microfilament-independent en-…”
Section: Mccoy Cells To Infection With Chlamydia Trachomatismentioning
confidence: 99%
“…It has been suggested that Ca 2+ may influence lysosomal degranulation in, e.g., polymorphonuclear leukocytes [24]. Thus, the local intracellular concentration of Ca 2 + may contribute to the inability of chlamydiae-containing endosomes to fuse with lysosomes [3,5]; (ii) interference with the availability of host cell-derived nutrient required for intracellular chlamydial growth and reorganization. The time-dependent effect of TFP (Table 1) suggests that its major effect coincides with the differentiation of elementary bodies into reticulate bodies.…”
Section: H Incubation To Reflect Both Attached and Internalized Chlamentioning
confidence: 99%
See 1 more Smart Citation